2022
DOI: 10.1111/birt.12610
|View full text |Cite
|
Sign up to set email alerts
|

CenteringPregnancy in the Netherlands: Who engages, who doesn’t, and why

Abstract: Background CenteringPregnancy (CP), a model of group antenatal care, was implemented in 2012 in the Netherlands to improve perinatal health; CP is associated with improved pregnancy outcomes. However, motivating women to participate in CP can be difficult. As such, we explored the characteristics associated with CP uptake and attendance and then investigated whether participation differs between health care facilities. In addition, we examined the reasons why women may decline participation and the reasons for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Women who decided to participate in CP differed in several characteristics from women who did not participate. 26 Theoretically, if women had been offered CP in the control period, we would have expected a comparable distribution of CP and IC participants. If we had performed a per protocol analysis, the CP group would have been compared with all women in the control period without differentiating between these potential participants (compliers) and potential nonparticipants (noncompliers).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Women who decided to participate in CP differed in several characteristics from women who did not participate. 26 Theoretically, if women had been offered CP in the control period, we would have expected a comparable distribution of CP and IC participants. If we had performed a per protocol analysis, the CP group would have been compared with all women in the control period without differentiating between these potential participants (compliers) and potential nonparticipants (noncompliers).…”
Section: Discussionmentioning
confidence: 97%
“…Women participating in CP only received more individual prenatal check‐ups if they had complications that did not require a referral to secondary care and after the last antenatal session in the period before giving birth. A previous study conducted in the Netherlands revealed that 87% of the CP participants attended 7 or more CP sessions 26 . Groups were facilitated by a certified midwife and a co‐facilitator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After all, not all women are willing or able to participate. [20][21][22] In addition, not all women who accept to participate are included in the same group. This is because a group consists of women of similar gestational age, ensuring the topics of the sessions are adapted to the phases and needs of the group.…”
mentioning
confidence: 99%